The promise and challenges of pharmacogenomics in psychiatry - Elaine Ah Gi Lo; Yi Min Wan; Cyrus Su Hui Ho (Annals, Academy of Medicine, Singapore)
Pharmacogenomics (PGx) is an expanding field within precision medicine that is poised to play a crucial role in optimising patient outcomes, particularly in the realm of psychiatry. The remission rate for the initial antidepressant prescribed in the Sequenced Treatment Alternatives to Relieve Depression (STAR*D) trial was only approximately 30%, underscoring the need for more personalised approaches to prescribing.1 For psychiatric patients who may show resistance towards pharmacotherapy, PGx offers promise in reducing adverse effects and enhancing therapeutic efficacy. Personalised pharmacotherapy provides reassurance and potentially mitigates the nocebo effects and somatic symptom exacerbation that are prevalent among these patients.